Biofilm formation of Tenacibaculum maritimum, a fish pathogenic bacteria, to evaluate the antimicrobial activity of fish skin mucus - Tejero, Marc; Sanahuja, Ignasi; Balsalobre, Carlos; Ibarz, Antoni; Madrid, Cristina; Fernandez-Alacid, Laura (Frontiers in Marine Science, 2025)
Biofilms, defined as aggregates of microorganisms embedded in a self-produced matrix of extracellular polymeric substances (EPS), are formed by most bacteria in both natural and pathogenic ecosystems. In aquaculture, biofilms pose a dual challenge: they confer recalcitrance to antimicrobials treatments and contribute to persistent infections by forming on facility surfaces such as tanks, nets, cages, and equipment. Tenacibaculum maritimum, the causative agent of tenacibaculosis, is responsible for significant economic losses in fish farming. Although the antibacterial activity of fish skin mucus against this pathogen has been evaluated in vitro, its effects on T. maritimum biofilms have not yet been determined. In this study, we provide a simple methodology for the in vitro formation and quantification of T. maritimum biofilms to monitor antibacterial properties of different compounds or substances, such as fish skin mucus. For this purpose, biofilm formation was assessed under varying culture volumes (200, 300, and 400 µL) and incubation times (24, 48, and 72 hours) in 48-well microplates. Then, the effects of gilthead seabream (Sparus aurata) skin mucus were evaluated on planktonic growth, biofilm formation, and biofilm dispersion, measuring both biomass and metabolic activity. Based on the tested volumes and incubation times, the optimal condition for biofilm formation was defined as 24 hours in MB at 25 ºC using 200 µL culture volume. These conditions supported the development of a biofilm (OD570>1.5 after crystal violet staining) while conserving time and mucus. Seabream mucus significantly impaired T. maritimum planktonic growth and biofilm formation in a concentration-dependent manner. Non-diluted mucus completely inhibited planktonic growth and biofilm metabolic activity, and reduced biofilm biomass by 81.16 ± 2.54%. In contrast, its effect on mature biofilms was limited, with reductions of approximately 50% in metabolic activity and 40% in biomass. This study provides a platform to assess how different fish culture conditions affect the host’s susceptibility to T. maritimum infections, which is crucial for preventing economic losses in fish farming. Additionally, it opens the door to studies analyzing the components of fish skin mucus responsible for its antibacterial activity, aiming to develop novel therapeutic compounds for targeting biofilms formed by this pathogen.